Membrane casting solution, raw material composition, mixed matrix membrane, preparation method and wastewater treatment method
By doping modified polytetrafluoroethylene micropowder into the permeable vaporized film, a strongly hydrophobic and high-throughput mixed matrix membrane was prepared, which solved the problem of poor permeability of the matrix membrane to alcohol ether solvents, and achieved efficient separation and cost reduction of alcohol ether pollutants in aqueous waste solvents.
Patent Information
- Application Number
- CN202510003586.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-02
AI Technical Summary
In the existing permeable vaporized membrane separation technology, the matrix membrane has poor permeability to alcohol ether solvents, making it difficult to efficiently separate alcohol ether contaminants in aqueous waste solvents.
By dispersing the modified polytetrafluoroethylene powder in the cast film liquid, a strongly hydrophobic, high-throughput permeable vaporization mixed matrix membrane is prepared. The membrane is doped with modified PTFE powder and is preferentially permeable to alcohol ether solvents.
It realizes efficient separation of alcohol ether pollutants in aqueous waste solvents. Compared with pure PDMS membranes, the penetration flux is increased by 35 to 45%, reducing equipment investment and operating costs.
Smart Images

Figure CN119633611A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of environmental protection and membrane separation technology, and in particular to a membrane casting solution, a raw material composition, a mixed matrix membrane, a preparation method, and a wastewater treatment method. Background Art
[0002] In recent years, with the rapid development of automobile demand, the production lines of many automobile manufacturers are constantly expanding, which has also led to a large amount of wastewater generated in automobile painting workshops, including aqueous waste solvents generated when using aqueous solvents to clean spray guns and paint pipelines. The aqueous waste solvent mainly contains complex components such as paint, organic solvents, surfactants and curing agents, and the dichromate index (CODcr) content is about 300,000 to 800,000 mg / L. At present, major painting workshops generally entrust this aqueous waste solvent as hazardous waste to qualified companies for incineration treatment, and the treatment cost is quite high.
[0003] For the industrial wastewater generated by this kind of painting workshop, the conventional treatment process first uses coagulation and sedimentation to remove paint, curing agent and other components in the wastewater, and then the coagulation supernatant is further removed by advanced oxidation technology to remove organic matter in it, and then the effluent enters the biochemical treatment system in the factory for further treatment, so as to meet the piped emission standards. At present, the existing treatment methods such as biochemical method, low-temperature evaporation technology, advanced oxidation technology, reverse osmosis membrane method, etc. have various problems such as too high organic load, azeotropic reaction of water and organic matter, unstable operation and high cost, and membrane material intolerance, which cannot be realized in engineering application.
[0004] Therefore, developing an efficient, environmentally friendly, economical and stable process to treat aqueous waste solvents has become a difficult problem in the environmental protection industry.
[0005] Pervaporation (PV) membrane separation technology is a new type of membrane separation technology. This technology is used for the separation of liquid mixtures. Its outstanding advantage is that it can achieve separation tasks that are difficult to complete with traditional methods such as distillation, extraction, and adsorption with low energy consumption. At present, pervaporation is mainly used for solvent dehydration, separation of organic solvents, and replacement or partial replacement of distillation, among which solvent dehydration has been applied on a large scale in industrial applications. The patent "A Water-Based Paint Wastewater Treatment System" with application number CN201920455502.1 mentions the use of pervaporation to treat aqueous waste solvents. The treated effluent can not only meet the biochemical treatment load requirements, but the concentrated solution separated by the membrane can also be returned to the production line for secondary use, realizing the reduction and resource utilization of aqueous waste solvents. At present, the functional layer of the pervaporation membrane is mainly polymethylsiloxane (PDMS). There are problems of uneven dispersion and unstable membrane performance in the preparation process of this type of membrane. Therefore, the use of inorganic particles, mainly including zeolite, silica, carbon molecular sieves, MOF, etc. to modify PDMS has become a hot research direction, because these inorganic particles can not only enhance the hydrophobicity of the membrane surface, but also overcome the shortcomings of organic polymer membranes such as poor mechanical strength and chemical stability.
[0006] For example, patents CN101264429A, CN107081068A, CN107519770A, CN 110180414A and CN 112999884A disclose the use of inorganic particles such as zeolite and silica to modify PDMS, which further demonstrates that doping with hydrophobic materials can indeed increase the permeation flux of the pervaporation composite membrane to treat organic matter. However, after the above inorganic particles modify PDMS, the pervaporation membrane has poor permeability to alcohol ether solvents.
[0007] Polytetrafluoroethylene (PTFE) powder is an organic fluorine-containing polymer and a common hydrophobic doping material. Patent CN104014259A discloses a method for preparing a hydrophobic separation membrane, wherein the hydrophobic monomers are fluorine-containing ethylene, fluorine-containing acrylate and fluorine-containing methacrylate, and the monomers contain 6 to 14 carbon atoms and 9 to 21 fluorine atoms. The main focus is on the study of membrane hydrophobicity, rather than preferentially permeating organic matter such as alcohol ethers, and even less on the treatment of aqueous waste solvents. Patent CN117732277A discloses a high-throughput super-hydrophobic composite membrane and a method for preparing the same, wherein PTFE submicron particles and three-dimensional nanomaterials are prepared into a microporous composite membrane with a micro-nano hierarchical structure, and used in vacuum membrane distillation technology to achieve salt removal in water bodies. The main focus is on the study of the desalination performance of the membrane, rather than preferentially permeating organic matter such as alcohol ethers, and even less on the treatment of aqueous waste solvents.
[0008] Therefore, how to provide a matrix membrane that can be used to preferentially permeate alcohol ether solvents in pervaporation membrane separation technology is a technical problem that needs to be solved urgently in the art. Summary of the invention
[0009] The technical problem to be solved by the present invention is to overcome the defect that the matrix membrane in the existing pervaporation membrane separation technology preferentially permeates alcohol ether solvents and has poor effect, and to provide a membrane casting liquid, a raw material composition, a mixed matrix membrane, a preparation method, and a wastewater treatment method.
[0010] The mixed matrix membrane in the present invention disperses PTFE micropowder through a silane coupling agent (for example, an ethanol solution of a silane coupling agent) to prepare a hydrophobic modified PTFE micropowder that preferentially permeates alcohol ethers. By doping the modified PTFE micropowder, a highly hydrophobic, high-throughput pervaporation mixed matrix membrane that preferentially permeates alcohol ethers can be prepared. The pervaporation mixed matrix membrane can efficiently separate alcohol ether pollutants in water-based paint waste liquid. Compared with a pure PDMS membrane, it can greatly reduce investment and operating costs, and further achieve energy conservation, emission reduction, cost reduction and efficiency improvement.
[0011] The present invention provides a raw material composition of a film casting solution, which comprises polysiloxane, a crosslinking agent, a solvent, modified polytetrafluoroethylene powder, and a catalyst;
[0012] The modified polytetrafluoroethylene micropowder comprises polytetrafluoroethylene micropowder and a silane coupling agent.
[0013] In the present invention, the type of polysiloxane can be any conventional type of polysiloxane in the art, such as hydroxyl-terminated polysiloxane.
[0014] In some embodiments of the present invention, the polysiloxane is polymethylsiloxane, such as polydimethylsiloxane.
[0015] In some embodiments of the present invention, the polysiloxane is hydroxyl-terminated polymethylsiloxane, for example hydroxyl-terminated polydimethylsiloxane.
[0016] In some embodiments of the present invention, the molecular weight of the polysiloxane is 1,000 to 100,000, for example, 10,000.
[0017] In some embodiments of the present invention, the polysiloxane is purchased from Jiangxi Xinghuo Factory.
[0018] In the present invention, the crosslinking agent may be a conventional crosslinking agent in the art that can crosslink polysiloxane, such as one or more of tetraethyl orthosilicate (TEOS), methyltrimethoxysilane, vinyltriethoxysilane, and also tetraethyl orthosilicate.
[0019] In the present invention, the solvent may be a conventional volatile solvent in the art, which can dissolve the polysiloxane and the crosslinking agent and does not participate in the polymerization reaction, such as one or more of n-heptane, toluene and n-hexane, and also n-heptane.
[0020] In the present invention, the polytetrafluoroethylene in the polytetrafluoroethylene powder can be conventional polytetrafluoroethylene in the art, such as polytetrafluoroethylene with a molecular weight of 10,000 to 100,000, polytetrafluoroethylene with a molecular weight of 50,000 to 100,000, and polytetrafluoroethylene with a molecular weight of 50,000.
[0021] In some embodiments of the present invention, the polytetrafluoroethylene is purchased from Dongguan Zhanyang Polymer Materials Co., Ltd.
[0022] In the present invention, the average particle size of the polytetrafluoroethylene powder may be a conventional average particle size in the art, such as 1 to 10 μm, and for example 2 μm.
[0023] In the present invention, the type of the silane coupling agent can be any conventional silane coupling agent in the art, such as one or more of KH-570, KH560 and KH550, preferably KH570, i.e., γ-methacryloxypropyltrimethoxysilane.
[0024] In the present invention, the mass ratio of the polytetrafluoroethylene powder to the silane coupling agent may be 10:(0.25-5.0), such as 10:1, 10:3 or 10:5.
[0025] In the present invention, the silane coupling agent in the modified polytetrafluoroethylene powder modifies the surface of the polytetrafluoroethylene powder to uniformly disperse the polytetrafluoroethylene.
[0026] In some embodiments of the present invention, the method for preparing the modified polytetrafluoroethylene micropowder comprises the following steps:
[0027] The dispersion containing the polytetrafluoroethylene micropowder and the silane coupling agent are mixed and modified to obtain the modified polytetrafluoroethylene micropowder.
[0028] The pH of the dispersion containing the polytetrafluoroethylene powder may be 8-10, for example, 9.
[0029] The pH of the dispersion containing the polytetrafluoroethylene powder can be adjusted by using a pH adjuster, such as ammonia water.
[0030] The solvent in the dispersion containing the polytetrafluoroethylene powder may be a conventional solvent in the art, such as ethanol, or 50% ethanol by volume.
[0031] In the preparation method of the modified polytetrafluoroethylene powder, the dispersion containing the polytetrafluoroethylene powder can be prepared by conventional methods in the art, for example, by mixing the polytetrafluoroethylene powder and a solvent and then dispersing the mixture by ultrasonication.
[0032] The ultrasonic dispersion time may be 10 to 20 minutes, for example 15 minutes.
[0033] In the method for preparing the modified polytetrafluoroethylene powder, the mixing process may be a conventional process in the art, for example, the silane coupling agent is added dropwise to the dispersion containing the polytetrafluoroethylene powder under stirring.
[0034] The stirring may be stirring with a pneumatic stirrer.
[0035] The stirring may be performed under a constant temperature condition.
[0036] The stirring temperature may be 20-30°C, for example 25°C.
[0037] Wherein, in the method for preparing the modified polytetrafluoroethylene powder, the silane coupling agent may be in the form of a solution containing the silane coupling agent, such as an ethanol solution containing the silane coupling agent.
[0038] In the solution containing the silane coupling agent, the mass concentration of the silane coupling agent may be 1-5%, for example, 3%.
[0039] In the method for preparing the modified polytetrafluoroethylene powder, the modification process can be a conventional process in the art, such as modification under rapid stirring conditions, modification under 800-1200 r / min conditions, and modification under 1000 r / min conditions.
[0040] Wherein, in the method for preparing the modified polytetrafluoroethylene powder, the modification temperature may be 20-30°C, for example, 25°C.
[0041] Wherein, in the method for preparing the modified polytetrafluoroethylene powder, the modification time may be 1 to 5 hours, such as 3 to 5 hours, and also such as 3 hours.
[0042] Wherein, in the preparation method of the modified polytetrafluoroethylene micropowder, the modification may further include steps such as centrifugation and drying.
[0043] The drying temperature may be 60-80°C.
[0044] In a preferred embodiment of the present invention, the method for preparing the modified polytetrafluoroethylene powder comprises the following steps:
[0045] The polytetrafluoroethylene powder is dispersed in an ethanol-ammonia solution, and then ultrasonically dispersed. Then, an ethanol solution of a silane coupling agent is added dropwise, and the mixture is rapidly stirred at 1000 r / min for modification. The modified polytetrafluoroethylene powder is then washed, centrifuged, and dried to obtain the modified polytetrafluoroethylene powder.
[0046] In the present invention, the average particle size of the modified polytetrafluoroethylene powder may be 1 to 10 μm.
[0047] In the present invention, the catalyst may be a conventional catalyst for catalyzing the reaction of polysiloxane and a crosslinking agent in the art, such as dibutyltin dilaurate.
[0048] In the present invention, the amount of the polysiloxane used can be the conventional amount of polysiloxane in the art, for example, the mass ratio of the polysiloxane to the crosslinking agent is 10:(0.75-1.25), and for example 10:1.
[0049] In the present invention, the amount of the catalyst used can be the conventional amount of catalyst used in the art, for example, the mass ratio of the catalyst to the cross-linking agent is (0.3-1.0):1, for example (0.3-0.5):1, and for example 0.5:1.
[0050] In the present invention, the amount of the solvent used can be the conventional amount of the solvent in the art, for example, the mass ratio of the solvent to the cross-linking agent is (20-100):1, for example (20-50):1, and for example 50:1.
[0051] In some embodiments of the present invention, the mass ratio of the modified polytetrafluoroethylene powder to the cross-linking agent may be (1-5):1, for example (2-5):1, and for example 2:1, 3:1, or 4:1.
[0052] In one embodiment of the present invention, the mass ratio of the polysiloxane, the cross-linking agent, the catalyst, the solvent and the modified polytetrafluoroethylene powder is 10:1:(0.3-0.5):(20-50):(2-5), for example, 10:1:0.5:50:2, 10:1:0.5:50:3 or 10:1:0.5:50:4.
[0053] The invention also provides a modified polytetrafluoroethylene micropowder, which consists of polytetrafluoroethylene micropowder and a silane coupling agent.
[0054] Wherein, the polytetrafluoroethylene powder can be as described above.
[0055] Wherein, the silane coupling agent can be as described above.
[0056] Wherein, the preparation method of the modified polytetrafluoroethylene powder can be as described above.
[0057] The present invention also provides a method for preparing a casting liquid, which comprises the following steps: reacting a raw material composition of the casting liquid to obtain the casting liquid.
[0058] In a preferred embodiment of the present invention, the method for preparing the casting solution comprises the following steps:
[0059] The polysiloxane, the cross-linking agent, the solvent and the modified polytetrafluoroethylene powder are mixed for the first time to obtain a mixture A;
[0060] Mixing the mixture A and the catalyst for a second time to obtain a mixture B;
[0061] The mixture B is reacted to obtain the casting solution.
[0062] In the present invention, the terms "first time" and "second time" have no special meanings and only indicate the order of mixing.
[0063] In the present invention, the first mixing can be performed under stirring conditions.
[0064] The stirring speed of the first mixing may be 800-1000 r / min, for example 800 r / min.
[0065] The stirring time of the first mixing may be 1 to 5 hours, such as 3 to 5 hours, and for example 3 hours.
[0066] In the present invention, the reaction time may be 10 to 30 min, such as 15 to 30 min, and for example 15 min.
[0067] In the present invention, the reaction temperature may be 20-30°C, for example 25°C.
[0068] In the present invention, the end point of the reaction may be the reaction until the viscosity of the casting solution reaches 30 to 50 mPa.s, for example, 40 mPa.s.
[0069] In the present invention, the viscosity of the casting solution may be 30-50 mPa.s, for example 40 mPa.s.
[0070] In the present invention, the viscosity can be measured by using a Heimerson ViscoliteXL7-100B portable viscometer.
[0071] In the present invention, the casting solution is generally subjected to a degassing post-treatment.
[0072] The degassing post-treatment method may be to stand for 0.5 to 1 hour, for example, 0.5 hour.
[0073] In the present invention, in the raw material composition of the casting solution, under the action of the catalyst, the polysiloxane and the cross-linking agent undergo a cross-linking reaction, and the product is generally PDMS with low surface energy.
[0074] The invention also provides a film casting solution, which is prepared by the method.
[0075] The present invention also provides a method for preparing a mixed matrix membrane, which comprises the following steps:
[0076] The casting solution is coated on the surface of the base film and solidified to obtain the mixed matrix membrane.
[0077] The coating thickness of the casting solution may be 5 to 300 μm, for example, 150 μm.
[0078] The coating method may be a conventional coating method in the art, such as blade coating.
[0079] The material of the base membrane may be a conventional supporting material in the art, such as a fluorine material, polyvinylidene fluoride (PVDF), or a polyvinylidene fluoride membrane purchased from Shenzhen Jiaquan Membrane Filtration Equipment Co., Ltd.
[0080] The curing temperature may be 60-100°C, for example 80°C.
[0081] The curing time may be 2 to 10 hours, such as 6 to 10 hours, and for example 6 hours.
[0082] Wherein, before the curing, the casting solution can be allowed to stand at room temperature for 1 to 2 hours, for example, 2 hours, after being coated on the base film layer.
[0083] The invention also provides a mixed matrix membrane prepared by the method.
[0084] The present invention also provides a mixed matrix membrane, which comprises a functional layer and a base membrane layer, wherein the functional layer comprises polysiloxane A and polytetrafluoroethylene powder and a silane coupling agent dispersed in the polysiloxane A;
[0085] The polysiloxane A is prepared by cross-linking reaction of polysiloxane and a cross-linking agent.
[0086] In some embodiments of the present invention, the polytetrafluoroethylene powder and the silane coupling agent may be as described above.
[0087] In some embodiments of the present invention, the polysiloxane may be as described above.
[0088] In some embodiments of the present invention, the functional layer is formed by solidifying the casting liquid.
[0089] The curing temperature may be 60-100°C, for example 80°C.
[0090] The curing time may be 2 to 10 hours, such as 6 to 10 hours, and for example 6 hours.
[0091] Wherein, before the curing, the casting solution can be left to stand at room temperature for 1 to 2 hours, for example, 2 hours, after being coated on the support layer.
[0092] The material of the base membrane layer may be a conventional supporting material in the art, such as polyvinylidene fluoride (PVDF), and also a polyvinylidene fluoride membrane purchased from Shenzhen Jiaquan Membrane Filtration Equipment Co., Ltd.
[0093] The present invention also provides a pervaporation membrane module, which comprises the mixed matrix membrane.
[0094] In a preferred embodiment of the present invention, the pervaporation membrane assembly comprises in sequence a first cover plate, a first graphite sealing gasket, a first mixed matrix membrane, a stainless steel support plate, a non-woven fabric, a second mixed matrix membrane, a second graphite sealing gasket and a second cover plate.
[0095] In a preferred embodiment of the present invention, a stainless steel guide layer is further provided between the mixed matrix membrane and the stainless steel support plate.
[0096] In a preferred embodiment of the present invention, in the pervaporation membrane module, the effective area of the mixed matrix membrane is 0.1 to 15 m 2 , for example 0.13m 2 .
[0097] In the present invention, the effective area refers to the area that can produce actual treatment effects during the wastewater treatment process.
[0098] The present invention also provides a pervaporation device, which comprises a pervaporation system, and the pervaporation system comprises the pervaporation membrane assembly.
[0099] In a preferred embodiment of the present invention, the pervaporation device comprises a feed liquid tank, a circulation pump, the pervaporation membrane assembly, a condensation system, and a vacuum pump.
[0100] In a preferred embodiment of the present invention, the liquid tank is placed in a heating device, such as a water bath.
[0101] In a preferred embodiment of the present invention, the condensation system may include a condensation tank and a cooling tank.
[0102] Wherein, the volume of the liquid tank can be 5 to 1000L.
[0103] The circulating pump can provide a stable flow rate on the feed liquid side, and the flow rate range can be 1 to 10 L / min, such as 5 L / min.
[0104] The total membrane area of the membrane stack that can be loaded in the pervaporation system can be between 0.1 and 15 m 2 Between, for example 0.1m 2 .
[0105] The pervaporation system is generally maintained at a temperature of 40-80°C, such as 65°C.
[0106] The condensation system can maintain a constant temperature of the permeate heat exchange device, and the pressure range is generally between -10 and 0°C, such as -5°C.
[0107] The vacuum pump can provide a constant pressure on the feed liquid permeation side, and the pressure range is 200-1000 Pa, such as 200-800 Pa, and also such as 800 Pa.
[0108] The present invention also provides a method for treating wastewater, which comprises the following steps:
[0109] The wastewater is treated by using the pervaporation device.
[0110] In the present invention, the waste water may be aqueous waste solvent or the aqueous ink washing waste liquid.
[0111] Wherein, the CODcr in the wastewater may be between 150,000 and 200,000 mg / L, for example, 178,000 mg / L or 192,000 mg / L.
[0112] The content of ethylene glycol monobutyl ether in the aqueous waste solvent may be 6.5-7.5 wt %, where the percentage refers to the mass percentage.
[0113] The total organic matter content in the aqueous waste solvent may be 13.5-15.5 wt %, where the percentage refers to the mass percentage.
[0114] The isopropyl alcohol content in the aqueous ink cleaning waste liquid may be 7.5-10 wt %, where the percentage refers to the mass percentage.
[0115] The total organic matter content in the aqueous ink cleaning waste liquid is 12.5-14.5wt%, and the percentage refers to the mass percentage.
[0116] In the present invention, the terms are explained as follows:
[0117] Polytetrafluoroethylene: Polytetrafluoroethylene, referred to as PTFE;
[0118] Polymethylhydrosiloxane: Polymethylhydrosiloxane, referred to as PDMS;
[0119] KH-570: γ-methacryloxypropyltrimethoxysilane;
[0120] Tetraethyl orthosilicate: Tetraethyl orthosilicate, TEOS;
[0121] Polyvinylidene difluoride: polyvinylidene difluoride, referred to as PVDF;
[0122] Dibutyltin Dilaurate T-12, referred to as DBTDL;
[0123] Dichromate index: dichromate oxidizability, referred to as CODcr.
[0124] Permeation flux: the amount of material that passes through a unit membrane area per unit time during membrane separation.
[0125] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0126] The reagents and raw materials used in the present invention are commercially available.
[0127] The positive and progressive effects of the present invention are:
[0128] (1) The present invention is the first to prepare a highly hydrophobic, high-flux pervaporation mixed matrix membrane that preferentially permeates alcohol ethers by doping modified PTFE micropowder, and apply it to the treatment of aqueous waste solvents from automobile painting. It can solve the problem of the outlet of such high-concentration organic hazardous wastes at low cost, high stability and high efficiency, and can better achieve its low-carbon reduction and resource utilization benefits.
[0129] (2) In the present invention, doped modified PTFE micropowder is used to prepare a pervaporation mixed matrix membrane. SEM shows that the PTFE micropowder is evenly distributed on the membrane surface and can form a relatively dense separation layer on the membrane surface, which can prevent water from passing through and preferentially pass alcohol ethers. In addition, the preparation method is simple and inexpensive, which provides a valuable reference for subsequent large-scale production.
[0130] (3) Compared with the pure PDMS membranes used in existing engineering applications, the pervaporation mixed matrix membrane prepared from the doped modified PTFE micropowder provided in the present invention can increase the permeation flux by 35-45%, greatly reducing equipment investment and operating costs, and achieving significant economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0131] Figure 1 This is a surface scanning electron microscope (SEM) image of the pervaporation mixed matrix membrane in Example 2.
[0132] Figure 2 Schematic diagram of the membrane assembly structure in Example 1-3 and Comparative Example 1-2.
[0133] Figure 3 Schematic diagram of the pervaporation process in Example 1-3 and Comparative Example 1-2.
[0134] in:
[0135] 201: flow guide layer, 202: graphite gasket, 203: pervaporation membrane, 204: stainless steel support plate with non-woven fabric;
[0136] 1: Liquid tank, 2: Heating device, 3: Water inlet pump, 4: Membrane assembly, 5: Condensation tank, 6: Cooling tank, 7: Vacuum pump. DETAILED DESCRIPTION
[0137] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0138] The following are the terms used:
[0139] Polytetrafluoroethylene: Polytetrafluoroethylene, referred to as PTFE;
[0140] Polymethylhydrosiloxane: Polymethylhydrosiloxane, referred to as PDMS;
[0141] KH-570: γ-methacryloxypropyltrimethoxysilane;
[0142] Tetraethyl orthosilicate: Tetraethyl orthosilicate, TEOS;
[0143] Polyvinylidene difluoride: polyvinylidene difluoride, referred to as PVDF;
[0144] Dibutyltin Dilaurate T-12, referred to as DBTDL;
[0145] Dichromate index: dichromate oxidizability, referred to as CODcr.
[0146] Permeation flux: the amount of material that passes through a unit membrane area per unit time during membrane separation.
[0147] In the following examples and comparative examples, the properties and sources of the raw materials are described as follows:
[0148] Polymethylsiloxane: molecular weight 10000, hydroxyl-terminated polydimethylsiloxane, purchased from Jiangxi Xinghuo Factory;
[0149] Polytetrafluoroethylene: molecular weight 50000, purchased from Dongguan Zhanyang Polymer Materials Co., Ltd.;
[0150] Polyvinylidene fluoride membrane: finished membrane, purchased from Shenzhen Jiaquan Membrane Filtration Equipment Co., Ltd.;
[0151] Molecular sieve: mesoporous molecular sieve SBA-15;
[0152] Zeolite: MFI type zeolite.
[0153] The viscosity was measured using a Heimerson ViscoliteXL7-100B portable viscometer.
[0154] Example 1
[0155] (1) Disperse polytetrafluoroethylene powder (the average particle size of the powder is 2 μm) in a 50% (50% refers to the volume concentration of ethanol) ethanol-ammonia aqueous solution at pH = 9, perform ultrasonic dispersion for 15 min, then stir with an air-driven stirrer at a constant temperature (25° C.), slowly dropwise add an ethanol solution containing 3% (the percentage refers to the mass concentration) of KH-570 (the mass ratio of polytetrafluoroethylene powder to KH-570 is 10:1), stir at a constant temperature (25° C.) for 3 h under rapid stirring (1000 r / min), then centrifuge the mixture, vacuum dry (60-80° C.), and grind to obtain modified polytetrafluoroethylene micropowder (the average particle size of the powder is 1-10 μm);
[0156] (2) 10 parts of PDMS, 1 part of TEOS, 50 parts of n-heptane, and 2 parts of modified polytetrafluoroethylene (PTFE) powder were mixed, stirred at 800 r / min for 3 h, 0.5 parts of DBTDL were added, and the reaction was continued at 800 r / min for 15 min (the reaction temperature was 25°C) until the reaction viscosity reached 40 mPa.s, then the stirring was stopped, and the mixture was allowed to stand for 0.5 h to degas for use;
[0157] (3) pouring the casting solution in (2) evenly onto the PVDF ultrafiltration membrane, coating it with a scraper to a certain thickness (wet film) on the surface of the base membrane, controlling the coating layer thickness to be 150 μm, and obtaining a liquid coating; leaving it to stand at room temperature for 2 hours, then transferring it to an oven, and heating it at 80° C. for 6 hours to obtain a PDMS / PVDF pervaporation mixed matrix membrane doped with polytetrafluoroethylene micropowder;
[0158] (4) Take 0.13m 2 (Effective size of single membrane: 0.205*0.16m, structure as Figure 2 The mixed matrix membrane assembly (as shown) was used on a test device to treat pre-treated aqueous waste solvent from a certain automobile factory and aqueous ink cleaning waste liquid from a printing factory. The CODcr of the feed liquid was between 150,000 and 200,000 mg / L. The pervaporation operation process parameters were: feed temperature of 65°C, vacuum degree of 800Pa on the gas phase side, condensation temperature of -5°C, and flow rate of 5L / min on the feed liquid side.
[0159] Example 2
[0160] (1) Disperse polytetrafluoroethylene powder (the average particle size of the powder is 2 μm) in a 50% (50% refers to the volume concentration of ethanol) ethanol ammonia solution at pH = 9, perform ultrasonic dispersion for 15 min, then stir with an air-driven stirrer at a constant temperature (25°C), slowly add dropwise a 3% (the percentage refers to the mass concentration) ethanol solution of KH-570 (the mass ratio of polytetrafluoroethylene powder to KH-570 is 10:3), stir at a constant temperature (25°C) for 3 h under rapid stirring (1000 r / min), then centrifuge the mixture, vacuum dry (60-80°C), and grind to obtain modified polytetrafluoroethylene micropowder (the average particle size of the powder is 1-10 μm);
[0161] (2) 10 parts of PDMS, 1 part of TEOS, 50 parts of n-heptane, and 3 parts of modified polytetrafluoroethylene (PTFE) powder were mixed, stirred at 800 r / min for 3 h, 0.5 parts of DBTDL were added, and the reaction was continued at 800 r / min for 15 min (the reaction temperature was 25°C) until the reaction viscosity reached 40 mPa.s, then the stirring was stopped, and the mixture was allowed to stand for 0.5 h to degas for use;
[0162] (3) pouring the casting solution in (2) evenly onto the PVDF ultrafiltration membrane, coating it with a scraper to a certain thickness (wet film) on the surface of the base membrane, controlling the coating layer thickness to be 150 μm, and obtaining a liquid coating; leaving it to stand at room temperature for 2 hours, then transferring it to an oven, and heating it at 80° C. for 6 hours to obtain a PDMS / PVDF pervaporation mixed matrix membrane doped with polytetrafluoroethylene micropowder;
[0163] (4) Take 0.13m 2 (Effective size of single membrane: 0.205*0.16m, structure as Figure 2The PDMS / PVDF pervaporation mixed matrix membrane assembly doped with polytetrafluoroethylene micropowder (as shown in the figure) was used on a test device to treat pretreated aqueous waste solvent from a certain automobile factory and aqueous ink cleaning waste liquid from a printing factory. The CODcr of the feed liquid was between 150,000 and 200,000 mg / L. The pervaporation operating process parameters were: feed temperature of 65°C, vacuum degree of 800Pa on the gas phase side, condensation temperature of -5°C, and flow rate of 5L / min on the feed liquid side.
[0164] Example 3
[0165] (1) Disperse polytetrafluoroethylene powder (the average particle size of the powder is 2 μm) in a 50% (50% refers to the volume concentration of ethanol) ethanol ammonia solution at pH = 9, perform ultrasonic dispersion for 15 min, then stir with an air-driven stirrer at a constant temperature (25°C), slowly add dropwise a 3% (the percentage refers to the mass concentration) ethanol solution of KH-570 (the mass ratio of polytetrafluoroethylene powder to KH-570 is 10:5), stir at a constant temperature (25°C) for 3 h under rapid stirring (1000 r / min), then centrifuge the mixture, vacuum dry (60-80°C), and grind to obtain modified polytetrafluoroethylene micropowder (the average particle size of the powder is 1-10 μm);
[0166] (2) 10 parts of PDMS, 1 part of TEOS, 50 parts of n-heptane, and 4 parts of modified polytetrafluoroethylene (PTFE) powder were mixed, stirred at 800 r / min for 3 h, 0.5 parts of DBTDL were added, and the reaction was continued at 800 r / min for 15 min (the reaction temperature was 25°C) until the reaction viscosity reached 40 mPa.s, then the stirring was stopped, and the mixture was allowed to stand for 0.5 h to degas for use;
[0167] (3) pouring the casting solution of (2) evenly onto the PVDF ultrafiltration membrane, coating it with a scraper to a certain thickness (wet film) on the surface of the base membrane, controlling the coating layer thickness to be 150 μm, and obtaining a liquid coating; leaving it to stand at room temperature for 2 hours, then transferring it to an oven, and heating it at 80° C. for 6 hours to obtain a PDMS / PVDF pervaporation mixed matrix membrane doped with polytetrafluoroethylene micropowder;
[0168] (4) Take 0.13m 2 (Effective size of single membrane: 0.205*0.16m, structure as Figure 2 The PDMS / PVDF pervaporation mixed matrix membrane assembly doped with polytetrafluoroethylene micropowder (as shown) was used on a test device to treat the pretreated aqueous waste solvent from a certain automobile factory and the aqueous ink cleaning waste liquid from a printing factory. The CODcr of the feed liquid was between 150,000 and 200,000 mg / L. The pervaporation operating process parameters were: feed temperature of 65°C, vacuum degree of 800Pa on the gas phase side, condensation temperature of -5°C, and flow rate of 5L / min on the feed liquid side.
[0169] Comparative Example 1
[0170] (1) 10 parts of PDMS, 1 part of TEOS, 50 parts of n-heptane, and 3 parts of mesoporous molecular sieve SBA-15 were mixed, stirred at 800 r / min for 3 h, 0.5 parts of DBTDL were added, and the reaction was continued at 800 r / min for 15 min (the reaction temperature was 25° C.) until the reaction viscosity reached 40 mPa.s, then the stirring was stopped, and the mixture was allowed to stand for 0.5 h to degas for use;
[0171] (2) pouring the casting solution of (1) evenly onto the PVDF ultrafiltration membrane, coating it on the surface of the base membrane with a certain thickness (wet film) using a scraper, controlling the coating layer thickness to be 150 μm, and obtaining a liquid coating; leaving it to stand at room temperature for 2 hours, then transferring it to an oven, and heating it at 80° C. for 6 hours to obtain a PDMS / PVDF pervaporation membrane;
[0172] (3) Take 0.13m 2 (Effective size of single membrane: 0.205*0.16m, structure as Figure 2 The PDMS / PVDF pervaporation membrane assembly (as shown) was used on a test device to treat pre-treated aqueous waste solvent from a certain automobile factory and aqueous ink cleaning waste liquid from a printing factory. The CODcr of the feed liquid was between 150,000 and 200,000 mg / L. The pervaporation operating process parameters were: feed temperature of 65°C, vacuum degree of 800Pa on the gas phase side, condensation temperature of -5°C, and flow rate of 5L / min on the feed liquid side.
[0173] Comparative Example 2
[0174] (1) 10 parts of PDMS, 1 part of TEOS, 50 parts of n-heptane, and 3 parts of MFI zeolite were mixed, stirred at 800 r / min for 3 h, 0.5 parts of DBTDL were added, and the reaction was continued at 800 r / min for 15 min (the reaction temperature was 25° C.) until the reaction viscosity reached 40 mPa.s, then the stirring was stopped, and the mixture was allowed to stand for 0.5 h to degas for use;
[0175] Steps (2) and (3) are the same as steps (2) and (3) in Comparative Example 1.
[0176] Effect Example 1
[0177] (1) Take the pervaporation mixed matrix membrane in step (3) of Example 2 and observe its surface scanning electron microscope (SEM) image. Figure 1 As shown, it can be seen through SEM that the modified PTFE powder (ie, modified polytetrafluoroethylene powder) in Example 2 is evenly distributed on the membrane surface, and can form a relatively dense separation layer on the membrane surface, which can prevent water from penetrating and preferentially permeate alcohol ethers.
[0178] (2) The pervaporation mixed matrix membrane modules in Examples 1 to 3 and Comparative Examples 1 to 2 were used to treat aqueous waste solvent and aqueous ink cleaning waste liquid, respectively. The CODcr of these feed liquids were all between 150,000 and 200,000 mg / L. The pervaporation operating process parameters were: feed temperature of 65°C, vacuum degree of 800 Pa on the gas phase side, condensation temperature of -5°C, and flow rate of 5 L / min on the feed liquid side.
[0179] The schematic diagram of the pervaporation process is as follows Figure 3 shown.
[0180] The raw materials tested are the aqueous waste solvents generated during the spraying and color changing process in the paint shop of the automobile factory and the high-concentration aqueous ink cleaning waste liquid generated during the printing and packaging process.
[0181] Among them, the content of ethylene glycol monobutyl ether in the aqueous waste solvent is 6.5-7.5wt%, the content of total organic matter is 13.5-15.5wt%, and the experimental influent CODcr is 178000mg / L.
[0182] Among them, the isopropanol content in the aqueous ink cleaning waste liquid is 7.5-10wt%, the total organic matter content is 12.5-14.5wt%, and the experimental influent CODcr is 192000mg / L.
[0183] Table 1 Comparison of the effects of treating aqueous waste solvent and aqueous ink cleaning waste liquid in the embodiments and comparative examples
[0184]
[0185]
[0186] According to Table 1, compared with Comparative Examples 1 to 2, the pervaporation mixed matrix membrane prepared by using doped modified PTFE micropowder in Examples 1 to 3 significantly improves the permeation flux of alcohol ether solvents, and can efficiently separate alcohol ether pollutants in aqueous paint waste liquid. It can be seen that the PDMS membrane modified by using inorganic particle molecular sieves, zeolites, etc. has poor permeability to alcohol ether solvents.
Claims
1. A method for preparing a casting solution, characterized in that: The method comprises the following steps: reacting a raw material composition of a casting solution to obtain the casting solution; The raw material composition of the casting solution comprises polysiloxane, a cross-linking agent, a solvent, modified polytetrafluoroethylene powder, and a catalyst; The modified polytetrafluoroethylene micropowder comprises polytetrafluoroethylene micropowder and a silane coupling agent.
2. The method for preparing a casting solution according to claim 1, wherein: The method for preparing the casting solution satisfies one or more of the following conditions: (1) The polysiloxane is polymethylsiloxane or hydroxyl-terminated polysiloxane, such as hydroxyl-terminated polydimethylsiloxane; (2) The molecular weight of the polysiloxane is 1000 to 100000, for example 10000; (3) The crosslinking agent is one or more of tetraethyl orthosilicate, methyltrimethoxysilane, and vinyltriethoxysilane, for example, tetraethyl orthosilicate: (4) The solvent is one or more of n-heptane, toluene and n-hexane, such as n-heptane; (5) The polytetrafluoroethylene in the polytetrafluoroethylene powder is polytetrafluoroethylene with a molecular weight of 10,000 to 100,000, for example, polytetrafluoroethylene with a molecular weight of 50,000 to 100,000; (6) The average particle size of the polytetrafluoroethylene powder is 1 to 10 μm, for example, 2 μm; (7) The types of the silane coupling agent are KH-570, KH560 and KH550, for example, KH570; (8) The mass ratio of the polytetrafluoroethylene powder to the silane coupling agent is 10:(0.25-5.0), for example, 10:1, 10:3 or 10:5; (9) The method for preparing the modified polytetrafluoroethylene powder comprises the following steps: Mixing and modifying the dispersion containing the polytetrafluoroethylene micropowder and the silane coupling agent to obtain the modified polytetrafluoroethylene micropowder; The pH of the dispersion containing the polytetrafluoroethylene powder may be 8-10, for example 9; The pH of the dispersion containing the polytetrafluoroethylene micropowder can be adjusted by using aqueous ammonia; The solvent in the dispersion containing the polytetrafluoroethylene micropowder may be ethanol, for example, ethanol with a volume fraction of 50%; In the preparation method of the modified polytetrafluoroethylene micropowder, the preparation method of the dispersion containing the polytetrafluoroethylene micropowder is: after mixing the polytetrafluoroethylene micropowder and a solvent, the dispersion is prepared by ultrasonic dispersion; the ultrasonic dispersion time can be 10 to 20 minutes, for example, 15 minutes; In the preparation method of the modified polytetrafluoroethylene powder, the mixing process is: under stirring conditions, the silane coupling agent is added dropwise to the dispersion containing the polytetrafluoroethylene powder; the stirring temperature can be 20 to 30° C., for example, 25° C.; In the preparation method of the modified polytetrafluoroethylene powder, the silane coupling agent may be present in the form of a solution containing the silane coupling agent, and the mass concentration of the silane coupling agent in the solution containing the silane coupling agent may be 1 to 5%, for example, 3%; In the preparation method of the modified polytetrafluoroethylene powder, the modification process may be: modification at 800 to 1200 r / min, for example, modification at 1000 r / min; In the preparation method of the modified polytetrafluoroethylene powder, the modification temperature may be 20 to 30° C., for example, 25° C.; In the preparation method of the modified polytetrafluoroethylene powder, the modification time can be 1 to 5 hours, for example 3 to 5 hours, and for example 3 hours; (10) The average particle size of the modified polytetrafluoroethylene powder is 1 to 10 μm; (11) The type of the catalyst is dibutyltin dilaurate; (12) The mass ratio of the polysiloxane to the crosslinking agent is 10:(0.75-1.25), for example 10:1; (13) The mass ratio of the catalyst to the cross-linking agent is (0.3-1.0):1, for example (0.3-0.5):1, and for example 0.5:1; (14) The mass ratio of the solvent to the cross-linking agent is (20-100):1, for example (20-50):1, and for example 50:1; (15) The mass ratio of the modified polytetrafluoroethylene powder to the cross-linking agent is (1-5):1, for example (2-5):1, and for example 2:1, 3:1, or 4:1; Preferably, the mass ratio of the polysiloxane, the cross-linking agent, the catalyst, the solvent and the modified polytetrafluoroethylene powder is 10:1:(0.3-0.5):(20-50):(2-5), for example, 10:1:0.5:50:2, 10:1:0.5:50:3 or 10:1:0.5:50:4; (16) The method for preparing the casting solution comprises the following steps: The polysiloxane, the cross-linking agent, the solvent and the modified polytetrafluoroethylene powder are mixed for the first time to obtain a mixture A; Mixing the mixture A and the catalyst for a second time to obtain a mixture B; The mixture B is reacted to obtain the casting solution; Wherein, the stirring speed of the first mixing may be 800-1000 r / min, for example 800 r / min; The stirring time of the first mixing may be 1 to 5 hours, for example 3 to 5 hours, and for example 3 hours; The reaction time may be 10 to 30 min, for example 15 to 30 min, and for example 15 min; The reaction temperature may be 20-30°C, for example 25°C; The end point of the reaction may be the reaction until the viscosity of the casting solution reaches 30-50 mPa.s, for example, 40 mPa.s.
3. A casting solution, characterized in that: The method for preparing the casting solution is adopted as claimed in claim 1 or 2.
4. A method for preparing a mixed matrix membrane, characterized in that: It includes the following steps: Applying the casting solution of claim 3 to the surface of the base film and curing it to obtain the mixed matrix membrane; The coating thickness of the casting solution may be 5 to 300 μm, for example, 150 μm; The coating method may be blade coating; The material of the base film may be a fluorine material, such as polyvinylidene fluoride; The curing temperature may be 60-100°C, for example 80°C; The curing time may be 2 to 10 hours, such as 6 to 10 hours, and for example 6 hours.
5. A mixed matrix membrane, characterized in that Prepared by the method for preparing a mixed matrix membrane as claimed in claim 4; Alternatively, the mixed matrix membrane includes a functional layer and a base membrane layer, the functional layer includes polysiloxane A and polytetrafluoroethylene powder and a silane coupling agent dispersed in the polysiloxane A; the polysiloxane A is prepared by crosslinking the polysiloxane as described in claim 1 or 2 and the crosslinking agent as described in claim 1 or 2.
6. A raw material composition of a casting solution, characterized in that: It contains polysiloxane, a cross-linking agent, a solvent, modified polytetrafluoroethylene powder, and a catalyst; The modified polytetrafluoroethylene micropowder comprises polytetrafluoroethylene micropowder and a silane coupling agent; The polysiloxane may be the polysiloxane as claimed in claim 2; The cross-linking agent may be the cross-linking agent as described in claim 2; The solvent may be the solvent as described in claim 2; The modified polytetrafluoroethylene powder may be the modified polytetrafluoroethylene powder as described in claim 2; The catalyst may be a catalyst as claimed in claim 2.
7. A modified polytetrafluoroethylene powder, characterized in that: The modified polytetrafluoroethylene micropowder is composed of polytetrafluoroethylene micropowder and a silane coupling agent; The polytetrafluoroethylene powder may be the polytetrafluoroethylene powder as claimed in claim 2; The silane coupling agent may be the silane coupling agent as claimed in claim 2.
8. A pervaporation membrane module, characterized in that: It includes the mixed matrix membrane as claimed in claim 5; Preferably, the pervaporation membrane assembly comprises, in sequence, a first cover plate, a first graphite sealing gasket, a first mixed matrix membrane, a stainless steel support plate, a non-woven fabric, a second mixed matrix membrane, a second graphite sealing gasket and a second cover plate; a stainless steel guide layer may also be included between the mixed matrix membrane and the stainless steel support plate; In the pervaporation membrane assembly, the effective area of the mixed matrix membrane can be 0.1 to 15 m 2 , for example 0.13m 2 .
9. A pervaporation device, characterized in that: It comprises a pervaporation system, the pervaporation system comprising the pervaporation membrane module according to claim 8; Preferably, the pervaporation device comprises a feed liquid tank, a circulation pump, the pervaporation membrane assembly, a condensation system, and a vacuum pump.
10. A method for treating wastewater, characterized in that: It includes the following steps: The wastewater is treated using the pervaporation membrane assembly as claimed in claim 8 or the pervaporation device as claimed in claim 9.
Citation Information
Patent Citations
Preparation of osmotic vaporizing alcohol permselective zeolite filling silicon rubber compound film
CN101264429A
Preparation method of hydrophobic separating membrane
CN104014259A
Pervaporation membrane and preparation method thereof
CN107081068A
Application of nanohybrid mixing matrix pervaporation membrane to separate volatile aromatic compounds
CN107519770A
Pervaporation membrane material and preparation method thereof
CN110180414A